936Descriptive study of healthy life expectancy in all secondary medical areas in Japan. (2nd September 2021) - Ojima, Toshiyuki; Hosokawa, Rikuya; Myojin, Tomoya; Aida, Jun; Kondo, Katsunori; Kondo, Naoki
Abstract: Background: Healthy life expectancy (HLE) is an index combined with mortality and morbidity. Monitoring HLE is useful to assess and stimulate health promotion policies/programmes. Though HLE in national or prefectural areas have often been observed, further data in smaller areas are required. The aim of the study is to reveal descriptive features of HLE in secondary medical areas, that is almost same as public health centre jurisdictions and median of population is 214 thousand, in Japan. Methods: HLE by gender in all 341 secondary medical areas were calculated using Sullivan method. Population data was used from resident registry. Mortality data was from vital statistics of total death in 2016-2018. Data of proportions of unhealthy people was from long-term care insurance data in 2017 using proportion of people with care level 2 (almost bed ridden level) or more severe. Finally, maps of HLE of all of Japan were drawn. Results: Means (standard deviations, maximums, minimums, means of ranges of 95% confidence intervals) of HLE at birth are 79.21 (0.86, 81.36, 76.90, 0.92) and 83.75 (0.62, 85.45, 81.99, 0.80) years for males and females, respectively. Areas with short HLE were prevalent in Tohoku region (northern part), while that with long HLE in Chubu region (central part). Conclusions: Descriptive features of HLE in smaller areas of all of Japan can be firstly clarified. Key messages: Monitoring HLE in local areas would be feasible and useful in some countries. Precision of HLE of areas of these population size would be acceptable.